Determinants of Tertiary Students’ Intention to Participate in the Agriculture Sector in Visayas, Region 8 Philippines - David, Jose Andres S.; Hoaqui Dencel F. , Hoaqui Dencel F.; Sanchez, Kenneth Anthony B.; Rosete , Marie Antoinette L. (AGUSPATI Research Institute, 2022)
The study examines the intention of the tertiary students to participate in the agricultural sector in Visayas, Region 8 Philippines. Data suggests a decreasing trend of labor participation towards the agriculture sector. The objectives of the study is to identify and evaluate the factors that affect the decision of the students to participate or pursue a career in the agriculture sector in Visayas and be able to provide effective recommendations that can help engage the labor force to pursue a career related to the development of the agriculture sector. The study explores and assesses the factors that influence the participation of tertiary students in the agriculture sector. The factors the study seeks to evaluate the significance of parent’s education, both the father and mother’s highest educational attainment, to tertiary students' intention to participate in the agriculture sector. In addition, the study explores the positive effects of students’ education, migration, and income; and the negative relationship of age towards the intention of tertiary students to participate in the agriculture sector. Consequently, the findings of the study delves into the proposing and crafting various strategies and initiatives policymakers may develop, to improve the awareness and increase agriculture literacy among the youth in the tertiary level of education